Sistem Pemerintahan Pastoral Sinodal Dan Implikasinya Bagi Hamba Tuhan - Sidianto, Daniel; Hermanto, Yanto Paulus; Abraham, Rubin Adi (Sekolah Tinggi Teologi Kharisma, 2022)
History records that there are several systems of Church government namely: First, the system of government of the Episcopal Church; second, The system of government of the Presbyterian Church; third, the system of government of the Congregational Church; Fourth, There is no system of Church government. All its management activities move by relying on the Holy Spirit. P there was a session of the GBI Synod in 2021 which it was stated that the Indonesian Bethel Church (GBI) stated that it adheres to the system of government of the Synodal Pastoral Church. The system of government of the Synodal Pastoral Church is a system of Church government that gives autonomous rights to the pastors of the congregation to administer their local Church. What is the biblical basis of the Synodal Pastoral Church's system of government? It is this policy that has implications for the decision of the pastors of the local Church congregation to remain faithful to join this GBI synod until its old age because its leadership can be passed on to the next generation in accordance with the expectations of the pastors of the local Church congregation. With the loyalty of the congregational pastors, it will lead to the enlargement of the second largest GBI synod in Indonesia. Sejarah mencatat ada beberapa sistem pemerintahan Gereja yaitu: Pertama, Sistem pemerintahan Gereja Episkopal; kedua, Sistem pemerintahan Gereja Presbiterian; ketiga, sistem pemerintahan Gereja Kongregasional; Keempat, Tidak ada sistem pemerintahan Gereja. Semua aktifitas manajemennya bergerak dengan mengandalkan Roh Kudus. Pada sidang Sinode GBI tahun 2021 yang lalu telah dicetuskan bahwa Gereja Bethel Indonesia (GBI) menyatakan menganut sistem pemerintahan Gereja Pastoral Sinodal. Sistem pemerintahan Gereja Pastoral Sinodal adalah sistem pemerintahan Gereja yang memberikan hak otonom kepada para gembala sidang untuk mengelola Gereja lokalnya. Bagaimanakah landasan Alkitab sistem pemerintahan Gereja Pastoral Sinodal? Kebijakan inilah yang berimplikasi kepada keputusan para gembala sidang Gereja lokal untuk tetap setia bergabung dalam sinode GBI ini hingga masa tuanya karena kepemimpinannya dapat diturunkan kepada generasi selanjutnya yang sesuai dengan harapan gembala sidang Gereja lokal. Dengan adanya kesetiaan para gembala sidang maka akan berujung pada pembesaran sinode GBI terbesar kedua di Indonesia.